Evaluasi Program Pembinaan Ruani dan Ekspektasi Warga Binaan/Narapidana Di Lapas Klas II B Sleman - Ahmad Barozi (MSI UMY, 2016)
Evaluasi Program Pembinaan Ruani dan Ekspektasi Warga Binaan/Narapidana Di Lapas Klas II B Sleman